Growth references for Tsimane forager‐horticulturalists of the Bolivian Amazon. Issue 3 (7th November 2016) - Blackwell, Aaron D.; Urlacher, Samuel S.; Beheim, Bret; von Rueden, Christopher; Jaeggi, Adrian; Stieglitz, Jonathan; Trumble, Benjamin C.; Gurven, Michael; Kaplan, Hillard
Abstract: Objectives: Growth standards and references currently used to assess population and individual health are derived primarily from urban populations, including few individuals from indigenous or subsistence groups. Given environmental and genetic differences, growth may vary in these populations. Thus, there is a need to assess whether international standards are appropriate for all populations, and to produce population specific references if growth differs. Here we present and assess growth references for the Tsimane, an indigenous population of Bolivian forager‐horticulturalists. Methods: Mixed cross‐sectional/longitudinal anthropometrics (9, 614 individuals; 30, 118 observations; ages 0–29 years) were used to generate centile curves and Lambda‐Mu‐Sigma (LMS) tables for height‐for‐age, weight‐for‐age, body mass index (BMI)‐for‐age, and weight‐for‐height (WFH) using Generalized Additive Models for Location Shape and Scale ( GAMLSS ). Velocity curves were generated using SuperImposition by Translation and Rotation ( SITAR ). Tsimane ≤5 years were compared to World Health Organization (WHO) standards while those >5 years were compared to WHO school age references. All ages were compared to published references for Shuar forager‐horticulturalists of the Ecuadorian Amazon. Results: Tsimane growth differs from WHO values in height and weight, but is similar for BMI and WFH. Tsimane growth is characterized by slow height velocity in childhood and early adolescent peak height velocity at 11.3 and 13.2 years for girls and boys. Tsimane growth patterns are similar to Shuar, suggesting shared features of growth among indigenous South Americans. Conclusions: International references for BMI‐for‐age and WFH are likely appropriate for Tsimane, but differences in height‐for‐age and weight‐for‐age suggest Tsimane specific references may be useful for these measures.